1999
DOI: 10.3171/jns.1999.90.6.1025
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular coil placement compared with surgical clipping for the treatment of unruptured middle cerebral artery aneurysms: a consecutive series

Abstract: Careful evaluation of the angioanatomy of unruptured aneurysms allows selection of the most appropriate treatment. However, for unruptured MCA aneurysms, surgical clipping appears to be the most efficient treatment option. Series of unruptured aneurysms are ideal for comparing treatment results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(70 citation statements)
references
References 32 publications
2
66
0
2
Order By: Relevance
“…In the series reported by Raftopoulos et al, 4 the proportion of aneurysms proposed for coil embolization was similar, but embolization of the MCAA was responsible for 41.7% of the total failures of this technique of treatment. In 1999, Regli et al 2,3 reported 85% of failures for the EVT of unruptured MCAAs. In addition, the authors of a recent series found that, on the basis of 3D imaging, only 16.1% of all MCAAs were suitable for EVT, and they obtained a complete occlusion rate of 86.8%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the series reported by Raftopoulos et al, 4 the proportion of aneurysms proposed for coil embolization was similar, but embolization of the MCAA was responsible for 41.7% of the total failures of this technique of treatment. In 1999, Regli et al 2,3 reported 85% of failures for the EVT of unruptured MCAAs. In addition, the authors of a recent series found that, on the basis of 3D imaging, only 16.1% of all MCAAs were suitable for EVT, and they obtained a complete occlusion rate of 86.8%.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the feasibility of EVT of MCAAs is greater than expected before. [2][3]8 However, a precise analysis of complications and anatomic results is needed to define the place of the EVT in the management of MCAAs. Overall, treatment-related adverse events with or without clinical modification were encountered in 13 patients (25.5%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Este é o principal diferencial em relação ao tratamento endovascular,estando de acordo com Regli e col. 23 . Quanto à idade dos pacientes e o tamanho dos aneurismas, embora alguns estudos estabeleçam limite para o tratamento cirúrgico 1,23 , o mais importante é a individualização, devendose levar em consideração outras comorbidades, facilidade do acesso cirúrgico e a experiência do cirurgião.…”
Section: Resultsunclassified
“…In addition, as suggested by Rodriguez and authors [15], the distribution of aneurysm locations in the ISAT study is significantly different from what was previously reported, with MCA aneurysms comprising only 14.0 % of all aneurysms in ISAT as compared to approximately 25.0 % in reported literature, suggesting a potential sampling bias that favors maximizing outcome in the coiling group. Furthermore, current available comparative studies and meta-analyses on MCA aneurysm treatment suggested slight to moderate advantage of clipping over coiling [24,30,31,42]. Therefore, further investigation is warranted for justification of endovascular therapy as a viable alternative to surgical therapy in definitive treatment of MCA aneurysms.…”
Section: Trend For Mca Aneurysm Managementmentioning
confidence: 99%